2021
DOI: 10.1037/ccp0000647
|View full text |Cite
|
Sign up to set email alerts
|

Day-level shifts in social contexts during youth cannabis use treatment.

Abstract: Objective: Social context plays a critical role in youth cannabis use. Yet few studies have examined if and when social contexts shift during cannabis use treatment. This study examined daily shifts in youths' social contexts with the goal of characterizing how specific social contexts (e.g., time with cannabis-using friends or siblings) relate to cannabis craving and use during cannabis treatment. Method: Participants were 65 cannabis users (51% male), ages 15-24 years, who participated in a double-blind rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 72 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…Another difference between adolescents and adults is the importance of peers in SU behaviors during adolescence (Chassin et al, 2016). Adolescent SU primarily occurs in the context of peers and a central target of interventions is shifting adolescents from social networks supportive of SU to social networks supportive of recovery (Meisel et al, 2021). Although most interventions for adolescent SU address the peer context (Hogue et al, 2018), no studies examined changes in adolescents’ social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Another difference between adolescents and adults is the importance of peers in SU behaviors during adolescence (Chassin et al, 2016). Adolescent SU primarily occurs in the context of peers and a central target of interventions is shifting adolescents from social networks supportive of SU to social networks supportive of recovery (Meisel et al, 2021). Although most interventions for adolescent SU address the peer context (Hogue et al, 2018), no studies examined changes in adolescents’ social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that RMCs were protective with respect to several non‐substance use recovery outcomes at certain periods in recovery, informing strategies for improving the timing and intensity of check‐ups [16]. Another recent study applied TVEM to understand how the time‐varying associations between time spent in social contexts (with substance‐using versus non‐using people) and craving unfold across time in recovery [53], showing that greater time spent with using friends increased craving among youth receiving cannabis treatment. Together, these results showcase the utility of TVEM, helping to delineate aspects of recovery that otherwise may be too complex to model.…”
Section: Discussionmentioning
confidence: 99%
“…An empirical demonstration: dynamic associations and moderation effects during early recovery Substance use researchers have been at the forefront of using TVEM with ILD, with investigations primarily involving the study of tobacco use/smoking behaviors and a few studies on alcohol use [41,[45][46][47][48][49][50][51], but only a few very recent investigations have used TVEM to study addiction recovery processes [16,17,52,53]. The present empirical study builds upon prior research by studying time-varying self-reported experiences of affect and craving and their associations with recovery outcomes (i.e.…”
Section: A Brief Overview Of Tvemmentioning
confidence: 99%
“…Emery et al (2020) used prerandomization data to examine how affect and situational cues relate to planned and unplanned cannabis use. Meisel, Carpenter, et al (2021) examined changes in day-level associations between cannabis-using peers, nonusing peers, cannabis craving, and grams used per day. Meisel, Padovano, and Miranda (2021) examined how time spent with cannabis-using versus nonusing peers related to cannabis use and craving.…”
Section: Appendixmentioning
confidence: 99%